2019
DOI: 10.12659/msm.916447
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Safety of In Vitro Fertilization (IVF)/Intracytoplasmic Sperm Injection (ICSI) Among Patients with Endometriosis After a Shortened Protocol of Long-Term Pituitary Downregulation

Abstract: Background Patients with endometriosis (EMs) are routinely advised to take GnRH-a for 3–6 months to improve the internal reproductive environment, but this may not be necessary. Material/Methods This retrospective study examined the effects of in vitro fertilization (IVF)/intracytoplasmic sperm injection (ICSI) with shortened (n=311) or conventional (n=213) long-term pituitary downregulation in EMs patients between January 2013 and July 2017. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 32 publications
1
17
0
Order By: Relevance
“…The quality of embryos, IR, and clinical PR were not statistically significant different among the women with endometriosis who received or did not receive the regimen. Supporting our data, a recent retrospective study showed that the shortened regimen and the ultralong regimen did not produce different pregnancy outcomes after ART (33).…”
Section: Tablesupporting
confidence: 88%
“…The quality of embryos, IR, and clinical PR were not statistically significant different among the women with endometriosis who received or did not receive the regimen. Supporting our data, a recent retrospective study showed that the shortened regimen and the ultralong regimen did not produce different pregnancy outcomes after ART (33).…”
Section: Tablesupporting
confidence: 88%
“…[ 11 ] A retrospective study reported that a 2‐month downregulation did not produce different pregnancy outcomes after ART. [ 25 ] But there was no published RCT that compare a 2‐month downregulation with long protocol.…”
Section: Discussionmentioning
confidence: 99%
“…We have carefully reviewed these papers, and found that the pituitary desensitization time of long-acting and short-acting GnRH agonist were same and short from 14 to 21 days before ovarian stimulation. Recently, the novel ovarian stimulation protocol, long-acting GnRH agonist long protocol in follicular phase, was proposed in IVF cycle [14][15][16][17][18][19]. In this protocol, the duration of pituitary desensitization is extended to more than one month before ovarian stimulation.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, long-acting GnRH agonist long protocol in follicular phase is proposed in controlled ovarian stimulation of IVF cycle [14][15][16][17][18][19]. During this protocol, a long-acting GnRH agonist triptorelin is given as a single dose for pituitary desensitization on day 2-3 of menstrual cycle.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation